Proyecto de factibilidad para la creación de la empresa productora de muebles de madera (comedores) y su comercialización en la ciudad de Quito - Luna Tacuri, Verónica Aidee (2016)
The general objective of this is to determine the feasibility of implementing a processing company of wooden furniture (dining) and marketing in the city of Quito, in which a methodology was applied in the determination of the various methods and techniques, such as Inductive method, the deductive method, the synthetic analytical method, the statistical method in the Technical interview, survey, literature review and review of literature were applied. In market research conducted in the city of Quito, with a sample of 400 families and 12 mills wooden furniture Weighted surveys used and have inferred the results and then perform market analysis, determining the Potential Demand of 436,385 families, a Royal Request 414,471 households, 89,111 Effective Demand dining furniture, offer 28,848 the dining table and unmet Demand 60,263 dining furniture, which allowed us to determine that the project can and should be performed by the results obtained in the analysis of demand, supply and levels of marketing this product. The unmet demand reflects the potential market that exists in the city of Quito for this product, with the following results: For the first year of project life is unmet demand: 60,263 wooden furniture ( dining room), of which the company will be providing the Installed Capacity of 1,610 wooden furniture, but will serve 1,127 dining furniture representing Capacity Utilization project, suitable equipment will be used, which will be guaranteed to get a quality product at reasonable prices. Determining project engineering process diagrams, characteristics of operation and management, technical requirements such as equipment, facilities, furniture and fixtures is developed. Also an administrative study determined as a Limited Liability Company was held, with the functional organizational structure to the hierarchical levels as are the legislative level, advisor level, aux level and operational level, as well as operating manuals, charts, that they served as a guideline for implementing a good organization. To implement the necessary investment company haciende to $ 67,766.51, with $ 37,766.51 of equity and Bank loan of $ 30,000. The financial evaluation shows the following results: According to the NPV of this project gives a positive value of $ 331,023.10, indicating that the project or investment is suitable. For this project, the IRR is 87.50 % and this value satisfactory to carry out the project, the time required to recover the original investment would be 1 year 11 months and 5 days for this project, the sensitivity values are less than one, therefore not affect changes in project costs and increased revenues decreased 48.5 % and 28.6%, respectively, ie the project is not sensitive to these changes.